2015
DOI: 10.1038/npp.2015.351
|View full text |Cite
|
Sign up to set email alerts
|

Differential Control of Cocaine Self-Administration by GABAergic and Glutamatergic CB1 Cannabinoid Receptors

Abstract: The type 1 cannabinoid receptor (CB1) modulates numerous neurobehavioral processes and is therefore explored as a target for the treatment of several mental and neurological diseases. However, previous studies have investigated CB1 by targeting it globally, regardless of its two main neuronal localizations on glutamatergic and GABAergic neurons. In the context of cocaine addiction this lack of selectivity is critical since glutamatergic and GABAergic neuronal transmission is involved in different aspects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 68 publications
(101 reference statements)
2
47
1
Order By: Relevance
“…Loss of function in mutant mice lacking CB 1 receptors in specific cell types allowed insights into their anatomical localization and a deeper understanding of their necessary role for several brain functions (Bénard et al, ; Han et al, ; Koch et al, ; Marsicano et al, ; Martín‐García et al, ; Monory et al, ; Monory, Polack, Remus, Lutz, & Korte, ; Soria‐Gómez et al, ). Conditional mutant mice lacking CB 1 receptors in astrocytes exhibit neither in vivo hippocampal long‐term depression nor the impairment of spatial working memory typically observed following acute cannabinoid treatment (Han et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of function in mutant mice lacking CB 1 receptors in specific cell types allowed insights into their anatomical localization and a deeper understanding of their necessary role for several brain functions (Bénard et al, ; Han et al, ; Koch et al, ; Marsicano et al, ; Martín‐García et al, ; Monory et al, ; Monory, Polack, Remus, Lutz, & Korte, ; Soria‐Gómez et al, ). Conditional mutant mice lacking CB 1 receptors in astrocytes exhibit neither in vivo hippocampal long‐term depression nor the impairment of spatial working memory typically observed following acute cannabinoid treatment (Han et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, CB 1 receptor density is not uniform through the regions expressing it. Actually, the use of mutant mice lacking the CB 1 receptor in specific brain cell populations served to identify low CB 1 receptor expression in cellular, subcellular, or intracellular compartments and to understand its physiological functions in those compartments (Monory et al, 2006(Monory et al, , 2007Puighermanal et al, 2009;Bellocchio et al, 2010;B enard et al, 2012;Han et al, 2012;Steindel et al, 2013;Ruehle et al, 2013;Soria-G omez et al, 2014;Busquets-Garcia et al, 2015;Mart ın-Garc ıa et al, 2015;Oliveira da Cruz et al, 2015). In this study, the hippocampus was chosen because it is one of the structures with the highest CB 1 receptor immunoreactivity in the brain (Herkenham et al, 1990;Mailleux and Vanderhaeghen, 1992;Matsuda et al, 1993;Tsou et al, 1998;Marsicano and Lutz, 1999;Egertov a and Elphick, 2000;Katona et al, 2006;Kawamura et al, 2006;Lud anyi et al, 2008;Katona and Freund, 2012;Steindel et al, 2013;Hu and Mackie, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of CB 1 receptor antibody (Table ) was assessed in previous publications (Bellocchio et al, ; Reguero et al, ; Bénard et al, ; Hebert‐Chatelain et al, ; Soria‐Gómez et al, ; Martín‐García et al, ). Furthermore, the specificity was tested in this study by applying the antibody to CB 1 ‐KO hippocampus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other interactions with the eCB/CB1 system could alter drug reward and intake. Indeed, one recent study demonstrated that deletion of CB1 from forebrain GABAergic neurons (including striatal MSNs) enhances DA release (Martín-García et al, 2016), indicating that CB1 receptors at multiple synapses regulate the neurochemical effects of cocaine, and perhaps other abused drugs (Miller et al, 2007). …”
Section: Cb1 Receptorsmentioning
confidence: 99%